2021
DOI: 10.1002/pds.5233
|View full text |Cite
|
Sign up to set email alerts
|

Risk of interstitial lung disease in patients treated for atrial fibrillation with dronedarone versus other antiarrhythmics

Abstract: Purpose To compare risks of interstitial lung disease (ILD) between patients treated with dronedarone versus other antiarrhythmics. Methods Parallel retrospective cohort studies were conducted in the United States Department of Defense Military Health System database (DoD) and the HealthCore Integrated Research Database (HIRD). Study patients were treated for atrial fibrillation (AF) with dronedarone, amiodarone, sotalol, or flecainide. Propensity score matching was employed to create analysis cohorts balanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Due to the similarity of its chemical structure, dronedarone has a similar mechanism of action to amiodarone through the blockade delayed rectifier potassium channel and increase in the ERP with subsequent decreased likelihood of reentry. However, the non-iodinated formulation subsequently has significantly lower rates of thyroid toxicity [ 100 ]. Initial studies have also found that dronedarone may have lower rates of pulmonary fibrosis, although hepatotoxicity rates are similar [ 100 , 101 ].…”
Section: Class III Medications: Potassium Channel Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the similarity of its chemical structure, dronedarone has a similar mechanism of action to amiodarone through the blockade delayed rectifier potassium channel and increase in the ERP with subsequent decreased likelihood of reentry. However, the non-iodinated formulation subsequently has significantly lower rates of thyroid toxicity [ 100 ]. Initial studies have also found that dronedarone may have lower rates of pulmonary fibrosis, although hepatotoxicity rates are similar [ 100 , 101 ].…”
Section: Class III Medications: Potassium Channel Blockadementioning
confidence: 99%
“…However, the non-iodinated formulation subsequently has significantly lower rates of thyroid toxicity [ 100 ]. Initial studies have also found that dronedarone may have lower rates of pulmonary fibrosis, although hepatotoxicity rates are similar [ 100 , 101 ]. To date, most large trials comparing amiodarone to dronedarone for efficacy have focused on atrial fibrillation management.…”
Section: Class III Medications: Potassium Channel Blockadementioning
confidence: 99%